UNIVERSITY EDUCATION AND ITS ROLE IN PROMOTING PROFESSIONAL AND ETHICAL PRACTICES FOR ACCOUNTING WORK, A FIELD STUDY IN ACADEMIC EDUCATIONAL INSTITUTIONS IN THE THI QAR GOVERNORATE - Hussein Ali Mohsen (American Journals, 2022)
The study purpose to identify the role of accounting education in educational institutions in promoting professional and ethical practices of the accounting profession because this profession has an important and vital impact on the financial, administrative and economic activity of the country. Statistical programs, and the researcher used the questionnaire method to enhance the results of the study that targeted educational institutions in Thi Qar Governorate.The results of the study proved the existence of a role for academic and practical accounting qualification in promoting professional and ethical practices of the accounting profession, and the study recommended the necessity of linking theoretical courses in educational institutions to the nature of the labor market applied in various economic institutions.
Keywords: accounting education, educational institutions, professional and ethical practices, the accounting profession.